A Companion to Medieval Rules and Customaries
1 online resource (452 pages)
Keywords: A Companion to Medieval Rules and Customaries offers an introduction to the rules and customaries of the main religious orders in medieval Europe: Benedictine, Cistercian, Carthusian, Augustinian, Premonstratensian, Templar, Hospitaller, Teutonic, Dominican, Franciscan, and Carmelite. As well as introducing the early history and spirituality of the orders, scholars survey the central topics - organization, doctrine, morality, liturgy, and culture, as documented by these primary sources. Contributors are: James Clark, Tom Gaens, Jean-François Godet-Calogeras, Holly Grieco, Emilia Jamroziak, Gert Melville, Stephen Molvarec, Carol Neel, Krijn Pansters, Matthew Ponesse, Bert Roest, Kristjan Toomaspoeg, Paul van Geest, Ursula Vones-Liebenstein, and Coralie Zermatten.